Peak Fat Oxidation Rate Is Closely Associated With Plasma Free Fatty Acid Concentrations in Women; Similar to Men - Frandsen, Jacob; Poggi, Axel Illeris; Ritz, Christian; Larsen, Steen; Dela, Flemming; Helge, Jørn W. (Frontiers in Physiology, 2021)
Introduction: In men, whole body peak fat oxidation (PFO) determined by a graded exercise test is closely tied to plasma free fatty acid (FFA) availability. Men and women exhibit divergent metabolic responses to fasting and exercise, and it remains unknown how the combined fasting and exercise affect substrate utilization in women. We aimed to investigate this, hypothesizing that increased plasma FFA concentrations in women caused by fasting and repeated exercise will increase PFO during exercise. Then, that PFO would be higher in women compared with men (data from a previous study). Methods: On two separate days, 11 young endurance-trained women were investigated, either after an overnight fast (Fast) or 3.5 h after a standardized meal (Fed). On each day, a validated graded exercise protocol (GXT), used to establish PFO by indirect calorimetry, was performed four times separated by 3.5 h of bed rest both in the fasted (Fast) or fed (Fed) state. Results: Peak fat oxidation increased in the fasted state from 11 ± 3 (after an overnight fast, Fast 1) to 16 ± 3 (mean ± SD) mg/min/kg lean body mass (LBM) (after ~22 h fast, Fast 4), and this was highly associated with plasma FFA concentrations, which increased from 404 ± 203 (Fast 1) to 865 ± 210 μmol/L (Fast 4). No increase in PFO was found during the fed condition with repeated exercise. Compared with trained men from a former identical study, we found no sex differences in relative PFO (mg/min/kg LBM) between men and women, in spite of significant differences in plasma FFA concentrations during exercise after fasting. Conclusion: Peak fat oxidation increased with fasting and repeated exercise in trained women, but the relative PFO was similar in young trained men and women, despite major differences in plasma lipid concentrations during graded exercise.